1999
DOI: 10.1139/w99-018
|View full text |Cite
|
Sign up to set email alerts
|

Cross-induction of pyrene and phenanthrene in aMycobacteriumsp. isolated from polycyclic aromatic hydrocarbon contaminated river sediments

Abstract: A polycyclic aromatic hydrocarbon (PAH)-degrading culture enriched from contaminated river sediments and a Mycobacterium sp. isolated from the enrichment were tested to investigate the possible synergistic and antagonistic interactions affecting the degradation of pyrene in the presence of low molecular weight PAHs. The Mycobacterium sp. was able to mineralize 63% of the added pyrene when it was present as a sole source of carbon and energy. When the enrichment culture and the isolated bacterium were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…2). Likewise, Molina et al observed that when Mycobacterium strains were exposed to phenanthrene, de novo protein synthesis was not required for rapid mineralization of pyrene (31). In addition, a majority of the pyrene-specific proteins found in strain 6PY1 were similar in sequence to enzymes responsible for phenanthrene degradation in Nocardioides strain KP7 (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…2). Likewise, Molina et al observed that when Mycobacterium strains were exposed to phenanthrene, de novo protein synthesis was not required for rapid mineralization of pyrene (31). In addition, a majority of the pyrene-specific proteins found in strain 6PY1 were similar in sequence to enzymes responsible for phenanthrene degradation in Nocardioides strain KP7 (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The low water solubility and high sorbtion capacity of PAHs are often found to greatly influence biodegradation, but other factors, including production of toxic or dead-end metabolites, metabolite repression, the presence of preferred substrates, and the lack of cometabolic or inducer substrates, must be considered when PAH persistence is evident (433,295). Understanding how these factors affect the transformation of and determining any given PAH is difficult; understanding the processes in natural environments when mixtures of PAHs and their myriad metabolites are present is more difficult, especially as the majority of work has focused on a narrow selection of species.…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%
“…For example, Molina et al (433) observed that, for both a mixed culture and Mycobacterium sp. strain M1, crossacclimation occurred between phenanthrene and pyrene metabolism in that pyrene-grown cells did not require new protein synthesis to degrade phenanthrene.…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%
“…As noted earlier, only very limited success has so far been achieved in the application of bioremediation technologies to PAH contaminated sites [110][111][112] and this is partly due to the lack of induction of the catabolic enzymes [113,114]. External addition of the inducers is generally neither a cost-effective nor an ecofriendly alternative.…”
Section: Expression Of the Degradative Genesmentioning
confidence: 99%
“…One of the problems in extrapolating laboratory bioremediation experiments to the fi eld has been the poor survival of the degrading strains in the fi eld environment [113][114]. The inoculated strains are affected by the predation of protists and competition with indigenous microorganisms for nutrients or electron acceptors.…”
Section: Survival Of the Degrading Strainmentioning
confidence: 99%